Nursing of a patient with incomplete intestinal obstruction treated by the ultrasound-enhanced penetration of Traditional Chinese Medicine (中药超声药物透入治疗1例不完全性肠梗阻的护理体会) - LIU Xu (刘旭) (Journal of International Translational Medicine Limited, 2023)
This paper summarized nursing management of a patient with incomplete intestinal obstruction treated by the ultrasound-enhanced penetration of Traditional Chinese Medicine. In addition to gastrointestinal decompression and retention enema, ultrasound-enhanced penetration of Traditional Chinese Medicine was carried out to relieve the abdominal distension and pain. Pain control strategy and psychological intervention were carried out to improve the recovery of the patient. (本文总结中药超声药物透入法治疗不完全性肠梗阻1例的护理经验。在常规胃肠减压、保留灌肠等措施基础上, 实施中药超声药物透入治疗, 并给予疼痛、心理等护理干预, 患者腹胀、腹痛缓解, 恢复正常排便。)